Assessing the Sex-Related Genomic Composition Diﬀerence Using a k-mer-Based Approach: A Case of Study in Arapaima gigas (Pirarucu) - Cavalcante, Renata Lilian Dantas; Ortega, Jose Miguel; de Souza, Jorge Estefano Santana; Sakamoto, Tetsu (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2020: Anais do XIII Simpósio Brasileiro de Bioinformática, 2020)
Arapaima gigas is the largest freshwater bony fish in the world, in which adults could weigh 200 kg and measure 3 m in length. Due to its large size and its low-fat meat, Arapaima gigas has quickly become a species of special interest in fish-farming. One challenge faced during their production is the lack of an eﬃcient sexing methodology, since their sexual maturation occurs late (around the third to the fifth year) and the genetic mechanisms linked to their sex determination system are not known yet. For a more sustainable management, it is of paramount importance to seek an eﬀective and non-invasive method to diﬀerentiate sexually juvenile individuals of Arapaima gigas. For this, the establishment of genetic markers associated with sexual diﬀerentiation would be an advantageous tool. In this study, we proposed a k-mer based approach to identify genome features with sex-determining properties. For this purpose, we used genomic data from six adult representatives of Arapaima gigas, three males and three females, and counted the k-mers comprising them. As result, we found k-mers from repetitive regions with high diﬀerence and disproportion in the count among individuals of the opposite sex. These diﬀerences in the k-mer-based genomic composition could indicate the existence of genetic factors involved in the sexing of individuals in Arapaima gigas.